2002
DOI: 10.1051/ocl.2002.0024
|View full text |Cite
|
Sign up to set email alerts
|

Production of unusual fatty acids in rapeseed

Abstract: Résumé : Les manipulations sur la qualité de l'huile chez les plantes cultivées sont d'un intérêt majeur et dépendent des modifications de la composition en huile des graines. Les acides gras habituels sont stockés sous forme de triacylglycérols. De nombreuses espèces accumulent des acides gras inhabituels (AGI) qui peuvent servir comme précurseurs à de nombreux produits chimiques ou encore conférer de nouvelles propriétés physiques ou chimiques aux huiles. L'isolement de gènes contrôlant la synthèse d'AGI a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Rapeseed is an important potential source of edible unsaturated oils. It is one of the most oleaginous plants cultivated in the world and it offers several advantages in the application of biotechnical approaches to improve oil composition [9,10]. Sebei et al [11] reported that two Tunisian rapeseed varieties (Hybridol and Pactol) contained more than 60% of oleic acid, 18% of linoleic acid, and 8% of linolenic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Rapeseed is an important potential source of edible unsaturated oils. It is one of the most oleaginous plants cultivated in the world and it offers several advantages in the application of biotechnical approaches to improve oil composition [9,10]. Sebei et al [11] reported that two Tunisian rapeseed varieties (Hybridol and Pactol) contained more than 60% of oleic acid, 18% of linoleic acid, and 8% of linolenic acid.…”
Section: Introductionmentioning
confidence: 99%
“…389). The development of transgenic plants to produce PUFA-and hydroxy-rich FFA and structured lipids has been reviewed (390)(391)(392)(393)(394)(395)(396)(397)(398)(399). As stated in a review by Jaworski and Cahoon (398) "the production of transgenic crop plants that efficiently synthesize and accumulate unusual FA is the next challenge" (p. 183).…”
Section: Other Biocatalytic Means Of Lipid Modificationmentioning
confidence: 97%
“…These seed-specific isoforms optimise channelling of unusual fatty acids into TAG and a segregation away from membrane lipids [13] (see Fig. 1).…”
Section: The Role Of Acyltransferases In the Biosynthesis Of Seed Lipidsmentioning
confidence: 99%